A novel performance-enhancing technique for concentrically braced frames incorporating square HSS. (15th December 2019) - Seker, Onur; Faytarouni, Mahmoud; Akbas, Bulent; Shen, Jay
Highlights: Majority of the tested square HSS braces fracture prior to 2.5% story drift ratio. Channel-encased braces offer a cost-effective performance-enhancing solution. Channel-encased braces increase energy dissipation capacity of braces by 3–4 times. Ductility demand in SCBFs is reduced by 2–3 times with channel-encased braces. Abstract: Structural performance in ductile concentrically braced frames (CBFs) can be generally associated with the plastic deformation capability of the bracing members. Considering the popularity of ductile CBFs incorporating square hollow structural shapes (HSS) in seismic areas, a simple and effective performance-enhancing technique for existing CBFs is developed. This paper discusses the hysteretic behavior of the developed channel-encased braces through finite element (FE) simulations and assesses the impact of the developed performance-enhancing technique on the seismic response of CBFs. For this purpose, first, the hysteretic stability of the braces has been examined through non-linear FE simulations. Then, the strain demands on the enhanced braces are compared with the conventional square HSS. Subsequently, a set of ductile CBFs designed in accordance with the current design codes are subjected to an ensemble of ground motion records to recognize the effect on the overall structural response. Our results point out that the developed enhanced braces are promising in terms of capability to improve cyclic stability, and consequently energy dissipation capacity of HSS by mitigating possibility of the potential failure modes that might take place in conventional HSS.